Isolation and Identification of Pathogenic Bacteria from Hospital Door Handles/knobs - Ghada Abougrara; Ghada Algeblaue; Enas Almabrouk; Ebtisam Almahdi (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives. Contracting infectious diseases from microbial contaminated door handles is a potential threat to health and safety. Therefore, we performed microbiological screening of door handles at the door handles of Zawia Education Hospital, Zawia, Libya, to estimate the presence of potentially pathogenic organisms. Methodology. A total of 125 samples were collected aseptically by using a moistened sterile bacteriologic swab on different days by scrubbing the selected handles and immersing them in the sterile broth to be transported to the microbiology laboratory, within no more than 30 minutes after collection. All the bacterial isolates were characterized and identified by standard diagnostic microbiological procedures and criteria, according to the Clinical and Laboratory Standards Institute. Data were presented as counts and percentages using Excel spread data sheath. Results: There was a total of 147 isolates obtained from the 12 sampled departments. The frequency of isolation of these organisms from these samples was as follows: coagulase-negative staphylococcus (16.80%) in 21 samples, Staphylococcus aureus (10.40%) in 13 samples, Diphtheroid (76.00%) in 95 samples, non-lactose fermenting gram negative bacilli (12.80%) in 16 samples, streptococcus pyogenes (0.80%) in one sample, and Klebsiella pneumoniae (0.80%) in one sample. Conclusion. Staphylococcus aureus, coagulase negative staphylococcus, streptococcus pyogenes, klebsiella pneumonae, Diphtheroid, and non-lactose fermenting gram-negative bacilli were the main bacteria isolated in this research study. The results of the present study demonstrated that contact surfaces such as door handles are often colonized by several bacteria and serve as a potential source of infections. الخلفية والأهداف. إن الإصابة بالأمراض المعدية من مقابض الأبواب الملوثة بالميكروبات تشكل تهديدا محتملا للصحة والسلامة. لذلك، قمنا بإجراء فحص ميكروبيولوجي لمقابض الأبواب عند مقابض أبواب مستشفى الزاوية التعليمي، الزاوية، ليبيا، لتقدير وجود الكائنات الحية المسببة للأمراض. طرق الدراسة. تم جمع 125 عينة بطريقة معقمة باستخدام مسحة بكتريولوجية معقمة مبللة في أيام مختلفة عن طريق فرك المقابض المختارة وغمرها في المرق المعقم لنقلها إلى مختبر الأحياء الدقيقة، خلال مدة لا تزيد عن 30 دقيقة بعد جمعها. تم تشخيص وتحديد جميع العزلات البكتيرية من خلال الإجراءات والمعايير الميكروبيولوجية التشخيصية القياسية، وفقا لمعهد المعايير السريرية والمخبرية. تم تقديم البيانات كأعداد ونسب مئوية باستخدام نظام اكسل. النتائج. كان هناك ما مجموعه 147 عزلة تم الحصول عليها من 12 القسم. وكانت نسبة تكرار عزل هذه الكائنات من هذه العينات كما يلي: المكورات العنقودية سلبية المخثرة (16.80%) في 21 عينة، المكورات العنقودية الذهبية (10.40%) في 13 عينة، الدفترويد (76.00%) في 95 عينة، سالبة لجرام غير متخمرة اللاكتوز. العصيات (12.80%) في 16 عينة، العقدية المقيحة (0.80%) في عينة واحدة، والكلبسيلا الرئوية (0.80%) في عينة واحدة. الاستنتاج. المكورات العنقودية الذهبية، المكورات العنقودية سلبية المخثرة، العقدية المقيحة، الكلبسيلة الرئوية، الخناق، والعصيات سلبية الغرام غير المخمرة للاكتوز هي البكتيريا الرئيسية المعزولة في هذه الدراسة البحثية. أظهرت نتائج الدراسة الحالية أن الأسطح الملامسة مثل مقابض الأبواب غالبًا ما يتم استعمارها بواسطة العديد من البكتيريا وتكون بمثابة مصدر محتمل للعدوى